PENERAPAN METODE DRILL UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT KERAJINAN MAKRAME SISWA KELAS VC SD NEGERI 138 PEKANBARU - Frarindha Dessy Megario; Zariul Antosa; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract     The problem studied in this research is the low skills of the students in the learning makrame Arts Culture and Skills. The purpose of this research is to improve skills in the classroom make makrame SDN 138 Pekanbaru with the adoption of the drill. This research is a class action consisting of 2 cycles. Based on the assessment skills Intial seen from the data, the average was 54.23 students in the class. After the implementation of the method of cyclus first drill, the average score of students increased to 63.11 and the second cyclus, the average score of students increased to 82.4. Based on the analysis of the above data it can be concluded that the application of the drill method can improve skills in classroom make makrame SDN 138 Pekanbaru.Key Words: Drill method, objects construction